Evaluation of Bacteria Isolated from Industrial Wastewaters in Removal of Lead - R Nayyeri (Majallah-i Dānishgāh-i ̒Ulūm-i Pizishkī-i Qum, 2012)
Background and Objectives: Lead is a metal which has the most destructive effect on infants and fetuses. Moreover, it has negative biochemical effects on all persons including the destructive effects on the kidneys, digestive system, intestine, joints, and reproductive system and may cause acute or chronic damage to the nervous system. The aim of this research was screening the bacterial biosorbents with high capacity for absorbing lead among other microorganisms. Methods: At first, by using medium containing of determined concentration of Pb(NO3)2, resistant bacterial isolates were received from three wastewater samples collected from the cities of Qom and Qazvin. Then, the Minimum Inhibitory Concentration of mentioned isolates was determined by agar dilution method. In order to identify isolates with metal uptake ability, a particular method (Pümpel et al, 1995) was used. At a later stage, biosorption capacity of lead for each isolate with metal uptake ability was investigated by using an Atomic Absorption Spectrophotometer. Finally, after selection and identification of two effective isolates in removal of lead, optimizing the biosorption conditions was carried out in several steps. Results: Out of 29 bacterial isolates that received, 15 lead resistant isolates with MIC≥7mM were selected in order to study lead uptake ability that resulted in selection of isolates Q-III and P-II with biosorption values of 162.8 mg g-1dw and 125.6 mg g-1dw, respectively. On the other hand, the maximum biosorption capacity of lead was observed by isolate Q-III in optimum conditions including contact time 2 h, pH 5, wet biomass concentration 0.5g and for isolate P-II in contact time 2 h, pH 5.5, wet biomass concentration 0.4 g. Conclusion: The results of this study indicated that bacterial isolates Bacillus sp. Q-III and Pseudomonas sp. P-II are two suitable biosorbents for the removal of Pb(II).